2014
DOI: 10.1016/j.jacc.2013.08.1649
|View full text |Cite
|
Sign up to set email alerts
|

Coil Embolization for Spontaneous Rupture of the Left Internal Mammary Artery Secondary to Lupus Vasculitis

Abstract: true2016-03-16T16:38:26

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…However, to our knowledge, there have been no reports of spontaneous rupture of the internal thoracic artery or mediastinal hematoma in patients with cirrhosis. During the literature review, we found a single case report of a large anterior mediastinal hematoma due to spontaneous internal thoracic artery rupture in a patient with underlying lupus vasculitis ( 9 ); similar to our case, the patient was successfully treated with coil embolization.…”
Section: Discussionsupporting
confidence: 76%
“…However, to our knowledge, there have been no reports of spontaneous rupture of the internal thoracic artery or mediastinal hematoma in patients with cirrhosis. During the literature review, we found a single case report of a large anterior mediastinal hematoma due to spontaneous internal thoracic artery rupture in a patient with underlying lupus vasculitis ( 9 ); similar to our case, the patient was successfully treated with coil embolization.…”
Section: Discussionsupporting
confidence: 76%